PRINSIP PRINSIP DALAM HUKUM KEPAILITAN DALAM PENYELESAIAN UTANG DEBITUR KEPADA KREDITUR - Herry Anto Simanjuntak (Universitas Quality, 2020)
In the world of trading, debt and credit is a common and natural thing if a business actor wants to develop his business more advanced, namely by seeking loans from other company partners to get business capital with an agreement to be paid later, and if able to pay according to the specified time then the company is in a